PENGGUNAAN STRATEGI READING ALOUD UNTUK MENINGKATKAN KETERAMPILAN PESERTA DIDIK DALAM MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR NEGERI 04 BENGKAYANG - Ajeng Kartini, Ricka Tesi Muskania; Sofhia Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the oral reading skills of third-grade students at SD Negeri 04 Bengkayang through the implementation of the reading aloud strategy. The research was motivated by students' low proficiency in reading with accurate pronunciation, intonation, and expression. This classroom action research employed the Kemmis and McTaggart model, conducted in two cycles using a descriptive quantitative approach. The subjects consisted of 28 students, and data were collected through oral reading tests, observations, and documentation. The results showed a significant improvement in students’ oral reading skills. The percentage of students who met the minimum mastery criteria increased from 14% in the pre-action stage to 60% in the first cycle and 89% in the second cycle. The average reading score also rose from 39.10 to 69.64. In addition to technical improvements, students demonstrated positive affective developments, including increased confidence, active participation, and expressive ability. These findings indicate that the reading aloud strategy is effective in enhancing both the technical and affective aspects of students' oral reading skills and can be recommended as an alternative instructional strategy for teaching Bahasa Indonesia in primary schools.